Organizational and pedagogical conditions for the implementation of the technological approach in preschool education - Shiiko V. D., Kazanskaia S. V. (Relevant Aspects of Pegagocics and Psychology, 2021)
the content of the article reveals theoretical positions on the implementation of a technological approach to the design of the educational process in a modern kindergarten.
Keywords: дошкольное образование; организационно-педагогические условия; управление дошкольным образованием; preschool education; organizational and pedagogical conditions; технологический подход в дошкольном образовании; preschool education management; technological approach in preschool education